THE ADOPTION OF SELF ORDERING MACHINE TECHNOLOGY BY CUSTOMERS AND THE INFLUENCE ON CUSTOMER SATISFACTION - Latif, Dini Verdania; Arsalan, Syakieb; Hadian, Niki; Octavia, Evi; Tresnawati, Rina; Mudzakar, Mochamad Kohar (CENTRAL ASIA AND THE CAUCASUS, 2022)
Increased competition among fast food restaurants, causing the restaurant to innovate. In accordance with developments in the current digital era, restaurants innovate by providing self-ordering machines. This study aims to determine the customer's willingness to adopt the machine and its effect on customer satisfaction based on the theory “Technology Acceptance Model (TAM)”. This research is a correlational research with the research sample is customers at fast food restaurants. Data analysis used regression analysis. The results of the study indicate that customers are willing to adopt self-ordering machines because these machines provide convenience and benefits in their use, so that customers feel satisfied. Ordering through machines can save ordering time and customers can order food according to their tastes.